How math happens at home: A Rasch-based validation of the home mathematics environment scale in early childhood - Nugraha, Adi Cahya; Rachmadani, Ira; Mardiana; Refiyanti, Nur Alifa Deviar; Soebagyo, Joko (Universitas Hamzanwadi, 2025)
Preschool education is important for developing children’s social and cognitive skills, with early mathematical ability being a strong predictor of future success. This study evaluated the psychometric properties of the Preschool Home Mathematics Questionnaire (PHMQ) using Rasch Model Analysis. A total of 95 parents and guardians of preschool-aged children participated in the study. A total of 37 Likert-scale items were analysed. The results showed excellent person reliability (0.93) and item reliability (0.96), indicating strong consistency and well-targeted item difficulty. Of the 37 items, 32 were valid according to the Rasch fit criteria, while five items (Q13, Q15, Q22, Q24, and Q26) showed misfit based on the Outfit mean square (MNSQ), Z-standard (ZSTD), and PTMEA-CORR. The Likert scale functioned well with ordered thresholds and smooth transitions between categories. The unidimensionality test confirmed that the PHMQ measures a single construct, with 44.1% of the variance explained and only 12.8% unexplained in the first contrast. While the PHMQ shows good validity and reliability, this study focused only on basic Rasch validation. Future research should explore differential item functioning (DIF), item bias, and long-term stability to further improve this instrument and support its use in different settings.